Relevansi Menyakiti Diri dengan Tingkat Kepuasan Pelaku Sebagai Bentuk Emosi Negatif - Jamuna Ulfah (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
Self injury is all too common in the age community. The environment, improper aducation and treatment can exacerbate the individual physically and psychologically. It underlies the research, to determine what causes the activity, its purpose and treatment. Through this research library study approach carried out. Studies indicate that: 1) the age at which a perpetrator is subjected to greater influence on treatment; 2) self injury may provide a distraction for the psychic sadness the perpetrator feels with a view to the full sensations of pleasure/relief, and 3) the treatment may include writing therapy and drawing therapy. The result is that self injury can be achived by any age group, based on unstable self control and environment and some other influence factors. The best way to alleviate symptoms is premature detection, and the most appropriate treatment is the creation of a supportive environment and full attention through the cultivation of spirituality, self appreciation and talent maximization.